2023
DOI: 10.1039/d3nj02293e
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the physicochemical and anti-biofilm properties of iota and lambda carrageenan-capped silver nanocomposites synthesized using response surface methodology

Abstract: Antimicrobial resistance of microbes due to the formation of biofilms is a global industrial, environmental, and health concern. The current study presents the synthesis, characterization, and functional assessment of two...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Moreover, RSM aided in characterizing nanocomposites and optimizing stability. Antibiofilm studies showcased the potency of these nanocomposites, especially in eradicating Pseudomonas aeruginosa biofilms, highlighting RSM’s role in enhancing their antibiofilm properties [ 23 ]. Gharbani et al (2023) demonstrated RSM’s ability to assess the synergistic antibacterial effect of natural compounds, offering an eco-friendly alternative to chemical preservatives.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, RSM aided in characterizing nanocomposites and optimizing stability. Antibiofilm studies showcased the potency of these nanocomposites, especially in eradicating Pseudomonas aeruginosa biofilms, highlighting RSM’s role in enhancing their antibiofilm properties [ 23 ]. Gharbani et al (2023) demonstrated RSM’s ability to assess the synergistic antibacterial effect of natural compounds, offering an eco-friendly alternative to chemical preservatives.…”
Section: Introductionmentioning
confidence: 99%